The past is present: a freethinker journalist, ideologies and loyal dissent - Rabe, Lizette (Department of Communication Science, University of the Free State, 2012)
South Africa has moved from an authoritarian state to a supposedly liberal democracy, with journalists as the assigned “watchdogs” of government. What can be learnt from a journalist who not only worked during apartheid South Africa, but also for a company whose raison d’être was to support the specific ethnic nationalist ideology of the government of the day? Rykie van Reenen is regarded by one South African historian as “undoubtedly the most outstanding Afrikaans journalist of the [twentieth] century”, later to be qualified by “possibly”. It is said her writing contributed in a significant way to the eventual change in Afrikaner Nationalist thinking. This article maps some of her dissentient writing to highlight her role as dissident journalist in a time of a kowtowing Afrikaans media sector. By referring to several examples, Van Reenen’s critical commentary on the Afrikaner Nationalist government will be discussed. Van Reenen can be called a freethinker, but her writing was still within Afrikaner Nationalism’s “loyal dissent” paradigm. The question arises: Can journalists free themselves from their own cultural backgrounds to become “watchdogs” of government and society? Taking into account that Van Reenen was critical of the government of the day, while still remaining an Afrikaner nationalist, with a lower case n, as she referred to herself, the author will ask how lessons can be learnt from the past and applied to the present. The article concludes with some observations on “independence” and “objectivity” as learned from the writings of Van Reenen.
Keywords: Journalism; South Africa